Decreased pericellular matrix production and selection for enhanced cell membrane repair may impair osteocyte responses to mechanical loading in the aging skeleton. Issue 1 (19th November 2019) - Hagan, Mackenzie L.; Yu, Kanglun; Zhu, Jiali; Vinson, Brooke N.; Roberts, Rachel L.; Montesinos Cartagena, Marlian; Johnson, Maribeth H.; Wang, Liyun; Isales, Carlos M.; Hamrick, Mark W.; McNeil, Paul L.; McGee‐Lawrence, Meghan E.
Abstract: Transient plasma membrane disruptions (PMD) occur in osteocytes with in vitro and in vivo loading, initiating mechanotransduction. The goal here was to determine whether osteocyte PMD formation or repair is affected by aging. Osteocytes from old (24 months) mice developed fewer PMD (−76% females, −54% males) from fluid shear than young (3 months) mice, and old mice developed fewer osteocyte PMD (−51%) during treadmill running. This was due at least in part to decreased pericellular matrix production, as studies revealed that pericellular matrix is integral to formation of osteocyte PMD, and aged osteocytes produced less pericellular matrix (−55%). Surprisingly, osteocyte PMD repair rate was faster (+25% females, +26% males) in osteocytes from old mice, and calcium wave propagation to adjacent nonwounded osteocytes was blunted, consistent with impaired mechanotransduction downstream of PMD in osteocytes with fast PMD repair in previous studies. Inducing PMD via fluid flow in young osteocytes in the presence of oxidative stress decreased postwounding cell survival and promoted accelerated PMD repair in surviving cells, suggesting selective loss of slower‐repairing osteocytes. Therefore, as oxidative stress increases during aging, slower‐repairing osteocytes may be unable to successfully repair PMD, leading to slower‐repairing osteocyte death in favor of faster‐repairing osteocyte survival. Since PMD are an important initiator of mechanotransduction, age‐related decreases in pericellular matrix and loss of slower‐repairing osteocytes may impair the ability of bone to properly respond to mechanical loading with bone formation. These data suggest that PMD formation and repair mechanisms represent new targets for improving bone mechanosensitivity with aging. Abstract : Pericellular matrix (blue) decreases during aging, which limits the number of membrane disruptions that form from a given load. Slower‐repairing osteocytes progressively succumb to repair failure from increasing oxidative stress during aging whereas rapidly repairing cells survive. Fast repair of membrane disruptions in surviving cells blunts their ability to propagate downstream mechanotransduction. Impaired formation of membrane disruptions during loading and rapid repair of membrane disruptions that do form may contribute to impaired bone adaptation in aged subjects.